REVIEW OF A SIMPLE POWERFUL POLARIZER FOR TESTING OF EDIBLE OIL QUALITY - Firdausi, Ketut Sofjan; Rahmawati, Henik (BERKALA FISIKA, 2015)
In this paper, we have shown that a simple pair of polarizer can be used to measure natural optical activity in total complex oil (vegetable oil and fats). A similar concept with quantum physics has been discussed to describe briefly the probability in finding a particle within certain region with the change of polarization due to the interaction light with saturated fatty acids. The light source was fluorescence lamp and the experimental condition was kept stable, i.e. constant temperature and constant humidity. The angle of polarization was measured repeatedly until 50 times. Our relative uncertainty measurement has been obtained up to 5% and this is obviously clear to be able to differentiate various different quality of oil. More important result is that ordinary light polarization can be used as powerful test to show various quality level of oils better than recent standard methods. A good prospect has also been obtained for halal level testing. It is found that average value of polarization in lard (pig oil) is relatively higher than the others.Keywords: polarization, oil quality, saturated fatty acid